1874-75 N.C. Sess. laws 280 - (:unkn) unknown (My University, 1875)
Ch. 207, §§ 1-2: That the Adjutant General be and he is hereby authorized, and directed, under the direction of the Governor, to draw if practicable such additional breech loading Springfield rifles, muskets and the accoutrements therefor as the State is entitled to, not to exceed four hundred, and to issue the same under the provisions of chapter ninety-six, acts of one thousand eight hundred and seventy-three and one thousand eight hundred and seventy-four, entitled an act to provide for and furnish arms to military schools.
Keywords: ARMED FORCES